The Study of Rice Production Potential on Sungai Bunut Irrigation Fields in Rawang Panca Arga District Asahan Regency - Noviyana Tanjung; Sumono Sumono; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2015)
Rawang Panca Arga District as the largest of centra rice production in Asahan Regency, must be studied its irrigation system of rice field to hold out and increase production. The purpose of this research was to study the rice production potential in Sungai Bunut irrigation fields in Rawang Panca Arga district Asahan regency in achieving the maximum level of rice production based on sun  radiation level, time to grow rice, and rice variety. This research also studied the ratio between irrigation field and crops field, the ratio between technical irrigation and pre technical and conventional irrigation and reliability of existing irrigation networks. In the year of 2009-2013, the results indicated that the irrigation network reliability was not good enough. The average ratio between technical irrigation and pre technical and conventional irrigation was 0,35, the average  ratio between irrigation field and crops field was 1,9 and the rice production target was 56,75%. keywords: rice, production target, production potential, irrigation network.